Implementasi S-MART Berdasarkan Undang-Undang Nomor 20 Tahun 2003 Republik Indonesia Tentang Sistem Pendidikan Nasional - Marjan Miharja; Wiend Sakti Myharto; Yasmin Noor Hanan Rusma; Fahim Achmad Rizaldi; Sandi Nugraha (Law Department, University of Widya Gama Mahakam Samarinda, 2021)
Background In Indonesian Law, number 20 at 2003 subsection 3 about National Education System stated that the functions of national education are to develop competence, also shape the character of people. Thus, develop among students’ competence to become religious people, clever, capable, creative, independent, also responsible for the country is also possible. After their parents, children learned at elementary school as a next step to the world. They will get everything that their need, such as culture and behaviour as the progress of learning and provision for their future life. The “S-MART” concept is the initial basis that must be applied to elementary schools, to build children's mental and behaviour in the future. Muhammadiyah 4 Kramat Jati Elementary School is one of the elementary schools that applies the “S-MART” concept to educating its students, it is hoped that the next generation will improve both in terms of morals and behaviour. The application of this concept also aims to learn children in an orderly manner. This is also in line with the law of the Republic of Indonesia number 20 of 2003 concerning the national education system so that every school increases the improvement of its students, to create a generation that is healthy and active in learning. Research methods This research method uses normative juridical research methods. The normative juridical research method is research on positive legal principles written in the legislation. Findings The results of this study are the initial data support obtained related to the optimization of staffing regulations to improve employee welfare in the Muhammadiyah Kramatjati environment after obtained. The researchers perform hypotheses and design R&D procedures in the form of roadmaps and research flow diagrams as well as the methodology that will be carried out in this study. Conclusion School as an educational institution should have a positive school culture to continuously improve its quality. A positive school culture will sow the values ​​of life and humanity so that schools can truly become agents of change to make Indonesian people who are complete, faithful and devoted to God Almighty and have a noble character, are healthy, knowledgeable, capable, creative, independent. and become a democratic and responsible citizen. School culture must be built based on the vision, mission and goals of the school by implementing participatory and open management so that it can truly be reached and internalized by all school members and stakeholders so that it can be implemented sincerely and consistently to achieve the goals set in the vision. and school goals. If implemented properly and consistently, school culture can improve its quality in an integrated manner for customer satisfaction, both internal and external customers.